Biocidal potential of electrochemically activated solutions (ECAS) against Aeromonas sp. Enterobacter sp. and Escherichia coli in tap water. (August 2020) - Ali, Sabtain; Khan, Sher Jamal; Allan, Richard; Hashmi, Imran
Abstract: The biocidal efficiency of electrochemically activated solutions (ECAS) against isolated bacterial species from the water distribution network was analyzed. Predominant microbial consortia (identified using 16S rRNA gene sequencing as Aeromonas sp. Enterobacter sp. and Escherichia . coli ) with a mean count of 1.15 × 10 6 CFU/mL was inoculated in 100 L tap water in a prototype network to simulate real conditions. The physico-chemical quality of tap water of subsurface origin was assessed before experimentation. The contact times of 10 s, 10 min and 1 h were selected against the ECAS dosages of 1%, 5% and 10% (v/v), respectively. Each test organism showed an independent response at varying dosages. A 10% disinfectant dosage corresponding to a contact time of 1 h showed the highest Log reduction as 4.11 > 3.50 > 2.74 for Enterobacter sp . > E. coli > Aeromonas sp., respectively. The results revealed that due to varying physico-chemical composition and carbon content of test water, complete inhibition of test organism (1.15 × 10 6 CFU/mL) was not achieved at 10% ECAS dosing for 1 h. The study concludes that adequate pretreatment could further enhance the removal efficacy and reduce the minimum inhibitory concentration of ECAS.